PEMBUATAN KOMPOS ANAEROB DENGAN MENGGUNAKAN KOMPOSTER SEDERHANA YANG DITERAPKAN DI DUSUN SIDOMULYO - Supardi Supardi; Elisa Sulistyorini (JPM17: Jurnal Pengabdian Masyarakat, 2020)
Organic waste from household can cause air pollution, produces stench. Actually, organic waste can be used to make compost. compost is very useful for fertilizing plants. The purpose of the enlightenment is making compost. The making compost education as an effort to empower low educate communities and optimize the use of organic waste to produce compost. Making compost also can improve skill of communities in Sidomulyo, Babakbowo, Gresik. The long term goal of this extension program is increasing the intelligence and provision of skills to be able to make their own compost and composter. The method that used in the community service program is counseling and assistance in making compost from organic waste. The step of this program began with the socialization and counseling of making compost and composter from household waste. The composter is made by using anaerob composter system. Keywords: Compost, Organic, Anaerob